Using Bayesian methods to update and expand the meta-analytic evidence of the five-factor model's relation to antisocial behavior. (February 2019) - Vize, Colin E.; Collison, Katherine L.; Miller, Joshua D.; Lynam, Donald R.
Abstract: The Five Factor Model (FFM) of personality is the dominant hierarchical model of personality. Previous work has demonstrated the importance of the FFM domains and facets in understanding a variety of antisocial behaviors ranging from non-violent antisocial behavior to a variety of aggression outcomes. The aim of the present meta-analysis was to quantitatively summarize the empirical work that has examined these relations, as well as update and expand previous work in this area using Bayesian meta-analytic methods. A comprehensive search of available literature on the FFM and antisocial behavior was conducted and posterior distributions of effect sizes were computed for the FFM domains (across 12 antisocial outcomes). The meta-analytic results supported the primary importance of (low) Agreeableness and (low) Conscientiousness in predicting antisocial behavior across antisocial outcomes, with the exception of the outcome related to child molestation. The importance of Neuroticism was more dependent on the specific antisocial outcome under examination. The results are discussed in the context of the descriptive research on the FFM and antisocial behavior, and how Bayesian methods provide additional utility in estimation and prediction compared to more common frequentist methods. Furthermore, we recommend that future work on the FFM and antisocial behavior move towards process-level analyses to further examine how traits are implicated in different forms of antisocial behavior. Highlights: Bayesian meta-analytic methods were used to examine the relation between the FFM domains and a variety of antisocial behavior (ASB) outcomes. Agreeableness was the strongest negative correlate of nearly all forms of ASB (except child molestation) followed by conscientiousness. Current results provide insights for etiological models of ASB and suggest potential directions for future intervention efforts.